ASSESSMENT THE RATIO OF LYMPHOPROLIFERATION PROCESSES TO LYMPHAPOPTOSIS IN MEN WITH PSYCHOACTIVE SUBSTANCE ABUSE IN THE NORTH OF RUSSIA - Mohammad Sohib Kabbani; Ekaterina Vasilievna Popovskaya; Elizaveta Yurievna Shashkova; Oksana Evgenievna Filippova; Lyubov Stanislavovna Shchegoleva (Медицинская иммунология)
AbstractUsing psychoactive substances can cause toxic encephalopathy, which contributes to the modulation of both innate and adaptive immune responses. The impact of the use of psychoactive substances, including those prohibited in the Russian Federation, on immune homeostasis remains insufficiently studied, especially in northern regions with extreme climatic factors. With regard to medical and social consequences, attention is drawn to the rapidly increasing social maladaptation of young patients, as well as the manifestation of organic damage to the central nervous system. This study is aimed at assessing the ratio of lymphoproliferation and lymphapoptosis processes in men with toxic encephalopathy caused by psychoactive substances in the conditions of the northern region. Materials and Methods: The work contains a comparative analysis of the immunological parameters of the peripheral blood of two groups of people living in the northern region of the Russian Federation: 20 men with toxic encephalopathy (mean age 33.8±1.8 years) on the first day after severe poisoning with psychoactive substances and 22 healthy volunteers (34.5±2.0 years; (control)). Phenotyping of peripheral blood lymphocytes was performed by the method of indirect immunoperoxidase reaction with monoclonal antibodies. Statistical data processing was performed using SPSS 25.0. The results revealed a statistically significant (p<0.01) increase in lymphocytes with the CD10+ marker in men with psychoactive substances abuse (0.54 (0.40-0.75) ×10⁹ cells/l) compared to the control (0.27 (0.16-0.51) ×10⁹ cells/l), which indicates hyperproliferation of lymphocytes due to CD10+. At the same time, a low number of lymphocytes with the CD95+ marker was recorded in men with psychoactive substances abuse compared to the control group, reflecting the suppression of apoptosis. A two-times increase in the CD10+/CD95+ ratio was established in men with psychoactive substances abuse, demonstrating an imbalance in proliferative-apoptotic processes. A distinctive feature for men with toxic encephalopathy is an increased content of CD10+ cells that stimulate immune responses via the classical pathway against the background of a low concentration of lymphocytes with the CD95+ marker, which indicates an increased expenditure of the reserve capacity of immune homeostasis and their reduction. A moderate decrease in the level of receptor expression (CD71+) on lymphocytes in men with psychoactive substances abuse was revealed. The data obtained indicate that in individuals with toxic encephalopathy in the conditions of the North, there is a disruption of both the long-term and short-term mechanisms for maintaining immune homeostasis due to an imbalance in the ratio of lymphoproliferation and apoptosis processes.